Physical nature of size effects in TiAlNiAu/GaN ohmic contacts to AlGaN/GaN heteroepitaxial structures - Torkhov N. A. Nikolay Aleksandrovich; Gradoboev A. V. Aleksandr Vasilyevich; Orlova K. N. Kseniya Nikolaevna; Toropov A. S. Aleksandr Sergeevich (2022, 2022)
Title screen